Resolving the dark matter of ABCA4 for 1054 Stargardt disease probands through integrated genomics and transcriptomics - Khan, Mubeen; Cornelis, Stéphanie S; Pozo-Valero, Marta Del; Whelan, Laura; Runhart, Esmee H; Mishra, Ketan; Bults, Femke; AlSwaiti, Yahya; AlTalbishi, Alaa; De Baere, Elfride; Banfi, Sandro; Banin, Eyal; et al. (Genetics in medicine, 2020)
PURPOSE: Missing heritability in human diseases represents a major challenge, and this is particularly true for ABCA4-associated Stargardt disease (STGD1). We aimed to elucidate the genomic and transcriptomic variation in 1054 unsolved STGD and STGD-like probands. METHODS: Sequencing of the complete 128-kb ABCA4 gene was performed using single-molecule molecular inversion probes (smMIPs), based on a semiautomated and cost-effective method. Structural variants (SVs) were identified using relative read coverage analyses and putative splice defects were studied using in vitro assays. RESULTS: In 448 biallelic probands 14 known and 13 novel deep-intronic variants were found, resulting in pseudoexon (PE) insertions or exon elongations in 105 alleles. Intriguingly, intron 13 variants c.1938-621G>A and c.1938-514G>A resulted in dual PE insertions consisting of the same upstream, but different downstream PEs. The intron 44 variant c.6148-84A>T resulted in two PE insertions and flanking exon deletions. Eleven distinct large deletions were found, two of which contained small inverted segments. Uniparental isodisomy of chromosome 1 was identified in one proband. CONCLUSION: Deep sequencing of ABCA4 and midigene-based splice assays allowed the identification of SVs and causal deep-intronic variants in 25% of biallelic STGD1 cases, which represents a model study that can be applied to other inherited diseases.
Keywords: mutace; ATP-Binding Cassette Transporters; Pedigree; introny; rodokmen; Genomics; lidé; ABC transportéry; Introns; Mutation; Macular Degeneration; ABCA4; structural variants; deep-intronic variants; makulární degenerace; transkriptom; Stargardt Disease; Transcriptome; Stargardt disease; smMIPs; Stargardtova nemoc; genomika; Humans